2023
DOI: 10.1021/acs.est.3c01541
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire-Derived Nitrogen Aerosols Threaten the Fragile Ecosystem in Himalayas and Tibetan Plateau

Abstract: Himalayas and Tibetan Plateau (HTP) is important for global biodiversity and regional sustainable development. While numerous studies have revealed that the ecosystem in this unique and pristine region is changing, their exact causes are still poorly understood. Here, we present a year-round (23 March 2017 to 19 March 2018) ground- and satellite-based atmospheric observation at the Qomolangma monitoring station (QOMS, 4276 m a.s.l.). Based on a comprehensive chemical and stable isotope (15N) analysis of nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This implies that while TDP and TDN share the same origin, TDP and TP do not. This relationship between TDP and TDN is to be put in perspective with the recent findings of Bhattarai et al who demonstrated that atmospheric N at QOMS is mainly driven by BB emissions . Our results corroborate these findings as they confirm that BB not only significantly contributes to bioavailable nitrogen in the Himalayas but also shows that it is the main source of bioavailable phosphorus too.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This implies that while TDP and TDN share the same origin, TDP and TP do not. This relationship between TDP and TDN is to be put in perspective with the recent findings of Bhattarai et al who demonstrated that atmospheric N at QOMS is mainly driven by BB emissions . Our results corroborate these findings as they confirm that BB not only significantly contributes to bioavailable nitrogen in the Himalayas but also shows that it is the main source of bioavailable phosphorus too.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorus and nitrogen are the key nutrients for any ecosystem and thus are likely to jointly influence the structure, functioning, and diversity of ecosystems, highlighting the importance of considering the N/P ratio for ecosystems. The concentrations of N species in aerosol at QOMS have been reported in our earlier publication . The TN/TP dry deposition ratios (i.e., F TN‑dry / F TN‑dry , calculated with F dry = C i V d , molar values) range from 0.905 to 79.0 with an average value of 15.5 ± 14.1 over QOMS.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations